Analisis Etika Komunikasi Bisnis Dalam Strategi Pemasaran Produk Di Sosial Media - Syafira, Dinda; Suhairi, Suhairi; Wulandari, Juwita Putri; Iswanti, Putri; Fauzi, Said Ihsan (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
The purpose of this study is to analyze corporate communication ethics in product marketing strategies on social media. This study examines the literature on the principles of business ethics and marketing communications. The method used is descriptive research, collecting information from primary and secondary sources. The analysis was carried out using a qualitative approach to identify the ethical aspects of product marketing in social networks. The aftereffects of this study demonstrate that there are several moral perspectives that need consideration in web-based entertainment business correspondence, such as genuineness, receptiveness, decency and social obligation. This study assists with understanding the decision and utilization of business correspondence morals in item advertising techniques via virtual entertainment. These discoveries can be the reason for building more moral business correspondence rehearses in the computerized period